Emerging research fields in safety and ergonomics in industrial collaborative robotics: A systematic literature review - Gualtieri, Luca; Rauch, Erwin; Vidoni, Renato (Robotics and computer-integrated manufacturing, 2021)
•Research in human–robot safety topics is more developed than in ergonomics.•There is a higher development in safety prevention aspects instead in protection.•All main research topics are increasing (on average) during the studied period.•Physical and cognitive ergonomics is growing significantly in the last two years.•Future developments should focus on the alignment of safety and ergonomics. Human–robot collaboration is a main technology of Industry 4.0 and is currently changing the shop floor of manufacturing companies. Collaborative robots are innovative industrial technologies introduced to help operators to perform manual activities in so called cyber-physical production systems and combine human inimitable abilities with smart machines strengths. Occupational health and safety criteria are of crucial importance in the implementation of collaborative robotics. Therefore, it is necessary to assess the state of the art for the design of safe and ergonomic collaborative robotic workcells. Emerging research fields beyond the state of the art are also of special interest. To achieve this goal this paper uses a systematic literature review methodology to review recent technical scientific bibliography and to identify current and future research fields. Main research themes addressed in the recent scientific literature regarding safety and ergonomics (or human factors) for industrial collaborative robotics were identified and categorized. The emerging research challenges and research fields were identified and analyzed based on the development of publications over time (annual growth).